Tumour and host cell PD-L1 is required to mediate suppression of anti-tumour immunity in mice - Janet Lau (Nature Portfolio, 2017)
PD-L1, the ligand for T-cell inhibitory receptor PD-1, can be expressed by various cell types in the tumour microenvironment. Here, the authors show that, in mouse models, the expression of PD-L1 from both cancerous and normal host immune cells is important for suppressing anti-tumour immune responses.